Primary epithelioid angiosarcoma of right hip joint: A case report and literature review. Issue 15 (April 2018) - Wang, Jin; Zhao, Min; Huang, Jin; Ang, Lin; Zheng, Li
Abstract: Rationale: Epithelioid angiosarcoma (EA) is a rare, highly invasive tumor. The histopathological features of EA are not distinct and less reported in the literature, and most of the medical records are incomplete. Patient concerns: A 61-year-old woman who came to the hospital because of pain in her right hip. This patient had had surgery for right hip tuberculosis 30 years ago. Diagnoses: The present study reports a case of primary EA of bone with aneurysmal bone cyst (ABC) that was diagnosed by 3 experienced pathologists. Interventions: The patients had undergone 2 surgeries; however, an early recurrence of the tumor was caused the death of the patient. Outcomes: Ten EA cases from other literature were reviewed in this article; all the symptoms were found in different parts of bone, and the case data were relatively complete. The primary clinical features and nonspecific histopathological morphology of the disease were summarized from the 11 cases mentioned in the literature, and the main immunohistochemistry characteristics and diagnostic traps of EA were reviewed. Lessons: Because the tumor has no characteristic diagnostic index in imaging and laboratory examination, the histopathologic features are not typical, especially in the case of obvious secondary lesions. It is easy to miss and misdiagnose. If possible, the diagnosis should be combined with immunohistochemical results.